A role for diacylglycerol kinase 4 in signalling crosstalk during Arabidopsis pollen tube growth. Issue 3 (17th February 2019) - Vaz Dias, Fernando; Serrazina, Susana; Vitorino, Miguel; Marchese, Dario; Heilmann, Ingo; Godinho, Margarida; Rodrigues, Mário; Malhó, Rui
Summary: Diacylglycerol kinases (DGKs) play a major role in the production of phosphatidic acid (PtdOH) and were implicated in endomembrane trafficking and signalling cascades. In plants, the role of DGKs is less clear, as PtdOH seems to arise mostly from phospholipase D activity. Here, we investigated the function of the Arabidopsis gene encoding DGK4, which is highly expressed in pollen. In vitro, pollen tubes from homozygous dgk4 plants showed normal morphology, but reduced growth rate and altered stiffness and adhesion properties (revealed by atomic force microscopy). In vivo, dgk4 pollen was able to fertilize wild‐type ovules, but self‐pollination in dgk4 plants led to fewer seeds and shorter siliques. Phenotypic analysis revealed that the dgk4 mutation affects not only the male germ line but also the vegetative tissue. DGK4‐green fluorescent protein fusion imaging revealed a cytosolic localization with a slightly higher signal in the subapical or apical region. dgk4 pollen tubes were found to exhibit perturbations in membrane recycling, and lipid analysis revealed a minor increase of PtdOH concomitant with decreased phosphatidylcholine, compared with wild‐type. In vitro, DGK4 was found to exhibit kinase and guanylyl cyclase activity. Quantitative PCR data revealed downregulation of genes related to actin dynamics and phosphoinositide metabolism in mutant pollen, but upregulation of the DGK6 isoform. Altogether, these results are discussed considering a role of DGK4 in signalling cross‐talk.